Study of the Subfamily Anabropsinae (Orthoptera: Anostostomatidae) in China V: Two new species of Anabropsis (Apteranabropsis) from Guangxi and phylogenetic analysis of the genus Anabropsis - Lu, Xiangyi; Lin, Li; Liu, Jing; Liang, Li Li; Bian, Xun (Zootaxa, 2022)
This paper is the fifth study of the subfamily Anabropsinae in China and contributes two new species from Guangxi, China, viz. Anabropsis (Apteranabropsis) multispinula sp. nov. (Chinese name: 多刺黯螽) and Anabropsis (Apteranabropsis) shii sp. nov. (Chinese name: 石氏黯螽). The paraproctal processes and male genitalia of Anabropsis (Apteranabropsis) tonkinensis Rehn, 1906 are illustrated. The entire mitochondrial genomes (mitogenomes) of three species of Anabropsis were sequenced. The complete mitochondrial genomes of A. (Apteranabropsis) multispinula sp. nov., A. (Apteranabropsis) shii sp. nov. and A. (Apteranabropsis) guangxiensis were 16023 bp, 16087 bp and 16148 bp in length, respectively. Entire mitogenome and all protein-coding genes (PCGs) displayed high AT-content values. Besides A. (Pteranabropsis) carnarius and A. (Apteranabropsis) guangxiensis, other species of Anabropsis were not found repeated elements in the A+T-rich region. The phylogenetic relationships were constructed among nine samples of eight species of Anabropsis and two outgroups based on 13 PCGs using both Bayesian Inference (BI) and Maximum Likelihood (ML). The phylogenetic analysis did not support for the monophyly of subgenus Apteranabropsis. It’s important to obtain more samples to derive accurate phylogenetic relationships.